Placental CRH as a Signal of Pregnancy Adversity and Impact on Fetal Neurodevelopment - Kassotaki, Ifigeneia; Valsamakis, Georgios; Mastorakos, George; Grammatopoulos, Dimitris K. (Frontiers in Endocrinology, 2021)
Early life is a period of considerable plasticity and vulnerability and insults during that period can disrupt the homeostatic equilibrium of the developing organism, resulting in adverse developmental programming and enhanced susceptibility to disease. Fetal exposure to prenatal stress can impede optimum brain development and deranged mother’s HPA axis stress responses can alter the neurodevelopmental trajectories of the offspring. Corticotropin-releasing hormone (CRH) and glucocorticoids, regulate fetal neurogenesis and while CRH exerts neuroprotective actions, increased levels of stress hormones have been associated with fetal brain structural alterations such as reduced cortical volume, impoverishment of neuronal density in the limbic brain areas and alterations in neuronal circuitry, synaptic plasticity, neurotransmission and GPCR signalling. Emerging evidence highlight the role of epigenetic changes in fetal brain programming, as stress-induced methylation of genes encoding molecules that are implicated in HPA axis and major neurodevelopmental processes. These serve as molecular memories and have been associated with long term modifications of the offspring’s stress regulatory system and increased susceptibility to psychosomatic disorders later in life. This review summarises our current understanding on the roles of CRH and other mediators of stress responses on fetal neurodevelopment.